HBR's 10 must reads : on managing yourself. Vol. 2 - Kolb, Deborah M.; Cross, Rob.; Badaracco, Joseph L.; Roberts, Laura Morgan. (HBR's 10 Must Reads., 2021)
From the preeminent thinkers whose work has defined an entire field to the rising stars who will redefine the way we think about business, here are the leading minds and landmark ideas that have established the Harvard Business Review as required reading for ambitious business people in organizations around the globe.